THE ROLE OF INVESTMENTS IN THE DEVELOPMENT OF THE NATIONAL ECONOMY - Tuxtamurodov, Davron (Science technology&Digital finance, 2023)
The article explores the socio-economic status of each area in managing the effective use of investments. The author's practical recommendations for ensuring the stability of the national economy by diversifying production, achieving the competitiveness of national goods in domestic and foreign markets, diversifying the composition and geography of exports have been put forward.